Kepemimpinan Dalam Pembentukan Blimbingsari Menjadi Desa Wisata - I Wayan Ruspendi Junaedi (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2014)
Government programs in the field of tourism planning seven million tourists visited Indonesia and at least four million of which visit the island of Bali in 2013. Mrs. Wendy, a stranger from Australia ever stayed in Blimbingsari said: "I do not want to dies before I see the Bali" others say "Bali is my second home". The tourist traffic has resulted in the flow of labor to Bali from outside Bali and overseas. With the presence of tourists and labor, the streets in Bali become dense and tourist spots are very crowded so that travel comforts were increasingly reduced. Congestion, environmental sustainability can no longer is maintained.It turns out the growth of tourism in Indonesia and especially Bali has created inequities in society. Villagers who live vigorously farming, preserve the environment, art, small industry and so did not feel anything from the glitter of tourism in Bali. Dollars that flow only be enjoyed by owners of capital who build hotels, art shops, industries and so on, whereas farmers who maintain agriculture, environment, the craft remained poor and did not enjoy the fruits of tourism. In addition, the construction carried out tends to turn off small businesses managed by local communities. That's why now developed tourist village. In December 2011 has been selected and assigned seven tourist villages of 8 districts in Bali. Seventh village is Village Pinge in Tabanan, Village Blimbingsari in Jembrana, Bedahulu village in Gianyar, Penglipuran village in Bangli regency, Pancasari village in Buleleng, Village Budakeling and Jasri village in Karangasem (interview with Rev. Suyaga Job), On December 25, 2011 the Regent has launched the Community Based Tourism Village Tourism Assocition (COBTA) Blimbingsari in Blimbingsari.